The association of myelin oligodendrocyte glycoprotein gene and white matter volume in obsessive-compulsive disorder - Atmaca, Murad; Onalan, Ebru; Yildirim, Hanefi; Yuce, Huseyin; Koc, Mustafa; Korkmaz, Sevda (Elsevier Science Bv, 2010)
Background: Morphological changes of white matter have been described in patients with obsessive-compulsive disorder (OCD). The aim of our study was to determine whether a functional polymorphism of the myelin oligodendrocyte glycoprotein (MOG) G511C (Val142Leu) is associated with white matter volumes in patients with OCD. Methods: The MOG G511C (Val142Leu) genotypes (Val/Val, Val/Leu and Leu/Leu) were determined for 30 patients with OCD and the same number of healthy controls. Magnetic resonance imaging (MRI) scans were obtained and analyzed by the software program. Results: In comparison with controls, while no difference in total brain volume and total gray matter volumes was seen, total white matter volumes of the patients were larger than those of healthy controls. The genotypic pattern of distribution of MOG G511C was not different between the OCD patients and the controls. ANCOVA analysis in the OCD patients revealed a significantly larger total white matter volumes in patients carrying the MOG G511C (Val142Leu) Val/Val genotype compared with those carrying the Val/Leu and Leu/Leu genotypes. The analyses revealed no significant effects of genotype in the combined group but there was a statistically significant diagnosis effect, and an interaction between diagnosis and genotype effect. Conclusions: Our study provides first evidence that the MOG G511C (Val142Leu) polymorphism might be associated with structural changes in the total white matter volumes of OCD patients, which might indicate an interaction between genetics and neuroimaging abnormalities in these patients. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: MOG; MRI; OCD; White matter